Exploring the role of DFI s in developing township economies - Molahloe, Matau (Graduate School of Business (GSB), 2025)
Townships are hubs of entrepreneurship with many micro and small businesses which provide opportunities for employment and poverty alleviation. The township economy, by virtue of our past, is often overlooked and underserved regarding economic development. The government has over the past few decades introduced initiatives to promote SMME development, particularly for township enterprises. Development Finance Institutions (“DFIs”) have emerged as significant facilitators in utilising their resources and financial know-how for direct investment into the township economy. DFIs have emerged as valuable institutions in supporting the township economy, bridging the gap between financial exclusion, and needed economic development. The research explores the role and effectiveness of DFIs in supporting the township economy. The study employed a qualitative research approach covering a sample of 3 representatives of the DFIs and 10 township entrepreneurs operating in Gauteng province from four townships of Tembisa, Soweto, Katlehong and Mamelodi using a semi-structured questionnaire for in-depth interviews. The study found that DFIs have a mandate to promote economic growth by providing financial and non-financial support where the market has failed to invest adequately. DFIs face a challenge as business support depends on the strict bankability factors resulting in a high failure rate for township businesses. In the absence of grants their performance is limited by their limited capacity and available capital. These factors limit penetration thus affecting the ability to materially transform the township economy. While there is evidence of considerable investments, job creation and value add administered into the townships because of DFI participation. SMMEs experience challenges in working with the DFIs which poses a risk to their overall effectiveness. SMMEs want to be part of the solutions and not to have the solutions presented to them. Based on the findings, it is recommended that to unlock the full potential of DFIs, they must adopt an integrated and inclusive approach, which focuses on the needs of the SMMEs being served. Policy reforms, legislation, and programs to create a favourable environment for local township SMMEs must be designed with their full participation. The government needs to invest in more innovative ways to improve bankability for the township entrepreneur. Given the low penetration rate, the focus should rather be on bankability incorporating special programs to incubate businesses. The government should make an allocation in its budget for grants towards DFIs as this will enable these institutions to make more advances at risk-free rates to boost economic growth.